Hearing screening in neonates admitted in neonatal intensive care unit at tertiary care centre of Southern Rajasthan - Roat, Santosh; Jain, Bhupesh; Sankhala, Ravikant; Das, Dipu (International Journal of Contemporary Pediatrics, 2024)
Background: Hearing impairment is a common congenital condition, significantly impacting speech and social development in children. Early detection and intervention are crucial for improving outcomes, yet many cases go undiagnosed. This study aims to identify hearing impairment among neonates in a tertiary care centre using otoacoustic emission (OAE) and auditory brainstem evoked response (ABER) screening methods. Methods: A prospective observational study was conducted in the paediatric department of RNT medical college, Udaipur, over six months. Newborns admitted to the neonatal intensive care unit were screened based on risk factors as per the joint committee on infant hearing guidelines. Inclusion criteria included high-risk factors such as low birth weight, mechanical ventilation (>5 days), APGAR score etc. Descriptive analysis was performed, with statistical significance assessed using the Chi-square test. Results: Of the 750 newborns screened, 64.67% passed bilaterally in first OAE screening, remaining were referred. Among referred babies, second OAE screening showed a referral rate of 16.9%. Significant associations were found between hearing impairment and risk factors such as low birth weight, low APGAR scores, and prolonged mechanical ventilation. ABER testing confirmed hearing impairment in 9 /140 tested infants, resulting in an incidence of 55.11 per 1,000 in high-risk infants and 3.2 per 1,000 in low-risk infants. The overall incidence was 12 per 1,000 infants. Conclusions: In high-risk group hearing impairment primarily associated with low birth weight and prolonged mechanical ventilation (>5 days), low Apgar score, ototoxic drug. In high-risk group hearing impairment (5.5%) was more than low risk group (0.32%).